Background lighting clutters: how do they affect visual saliency of urban objects?. Issue 1 (3rd April 2017) - Davoudian, Navaz
Abstract: The current study aims to create some general guidance for designers to better understand the impact of background lighting in their design and as a result minimize its effect on the visual saliency of urban objects. There are few studies about how lighting clutters can affect and decrease the visual saliency of illuminated urban objects at night. Lack of information in this area has resulted in increasing luminance to be recognized as one of the main tools to enhance the saliency of urban objects at night. To address this matter a study was performed to investigate the effect of proximity of lighting clutters on visual saliency of urban objects. A forced choice pair comparison method was employed, in which two test images of an urban object in different conditions of luminance contrast and proximity of light patterns were compared. Test participants reported in which image the target appeared more salient. Results show there is a progressive increase in saliency value by increasing the gap between the target and the background lighting when the luminance contrast of the target is three or higher. However, the critical area around the object with the highest effect lies between 0.5° and 1° visual angle. Removing light patterns beyond that point creates negligible effect. The findings of this study could inform development of future models of visual recognition in the road environment, models which can address the important effects of environmental context in addition to photometric variables (luminance and contrast) that are the only factors considered in traditional models of 'Visibility Level.'